The invasive land flatworm Obama nungara in La Réunion, a French island in the Indian Ocean, the first report of the species for Africa - Justine, Jean-Lou; Marie, Amandine Delphine; Gastineau, Romain; Fourcade, Yoan; Winsor, Leigh (Zootaxa, 2022)
The land flatworm Obama nungara, a species originating from South America and already invasive in many European countries, is recorded from La Réunion, a French island in the Indian Ocean. This is the first record of O. nungara from this locality and also the first record of the species for Africa. Three specimens were collected in 2021 and 2022, in the communes of Saint Paul, Saint Joseph and Le Tampon, respectively; the three localities are widely separated, with two in the Western part and one in the South-eastern part of the island. This suggests that the species is already present in several locations in La Réunion, and it is likely that the species is already present since 2020. The specimen from Saint Paul had the same cox1 haplotype as specimens previously recorded from several countries of Europe; it is hypothesized that the species was imported from Europe, probably from France. We mapped climatic suitability of the species in La Réunion and found that O. nungara could potentially invade a large part of the island. One record was apparently associated with the transport of plates of travertine, a construction material which has numerous cavities thus suitable for the transport and survival of adult or cocoons of land flatworms.